Effect of Intercropping on Latex Physiological Parameters and it’s Economic Impact at Juvenile Phase of Para Rubber (Hevea brasiliensis Mull. Arg.) - Yarin, Toko; Medda, P. S.; Murmu, Dipak Kumar; Uppar, Jyoti (International Journal of Bio-resource and Stress Management, 2024)
An experiment was carried out during January, 2020–21 and December, 2021–22 at Horticulture instructional farm, Uttar Banga Krishi Viswavidyalaya, Pundibari, West Bengal, India to find out the performance of growth and latex physiological parameters as well as the effect of intercropping on latex physiological parameters and its economic impact at juvenile phase of Para rubber (Hevea brasiliensis Mull. Arg.). The experiment was laid out in Randomized Block Design with three times replication comprising with 15 treatment combination. The five different clones were namely RRII 105, RRIM 600, RRII 430, RRII 429 and RRII 114. The results showed that clone RRII 430 excelled with regards to growth behavior followed by RRII 429 and RRII 414. However, RRIM 600 demonstrated its superiority in terms of latex physiological parameters apart from DRC% and TSC%. Highest average dry rubber content was observed in clone RRII 105 (40.28%) and total solid content in RRII 430 (68.43%). The positive impact of intercropping specially with annual crops on growth parameters were observed in various rubber clones due to continuous cultural management and inclusion of legumes in the cropping system and proved the profitability of the system with better remuneration to the growers. Intercropping with short duration crops with in most of the clones, improved plant growth, allowing the plant to reach tappable girth sooner compared to sole cropping under North Bengal agroclimatic situation.